Linking Psychological Capital and Behavioral Support for Change: The Roles of Openness to Change and Climate for Innovation - Liu, Jieqiong (Frontiers in Psychology, 2021)
Employees’ behavioral support for change is seen as a key factor for the success of organizational changes. Given the assumed importance, the study developed a multilevel conditional mediation model and examined whether psychological capital influences behavioral support for change and if so, how the effect occurs. Results from a sample of 69 team leaders and 319 followers showed that the positive impact of psychological capital on openness to change was stronger in teams high in climate for innovation and that the mediating role played by openness to change in the relationship of psychological capital to behavioral support for change was significant when climate for innovation was high.